2000
DOI: 10.1089/107999000414826
|View full text |Cite
|
Sign up to set email alerts
|

IFN-γ Enhances Osteoclast Generation in Cultures of Peripheral Blood from Osteopetrotic Patients and Normalizes Superoxide Production

Abstract: Interferon-gamma (IFN-gamma) treatment increases osteoclastic bone resorption in vivo in patients with malignant osteopetrosis (OP). The treatment effect was studied in vitro in osteoclasts generated by culturing peripheral white blood cells (PWBC) from OP patients and normal human control subjects. Osteoclasts were treated with or without IFN-gamma prior to the end of the culture period. Osteoclasts from normal subjects were large in size (161 +/- 18 microm in diameter) with >10 nuclei per osteoclast. These c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0
1

Year Published

2001
2001
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 28 publications
2
35
0
1
Order By: Relevance
“…A Pit Assay-Bone resorption was determined by a pit assay as described (12). Osteoclasts were isolated from the bone marrow of 4 -6-day-old neonatal mice and placed on bovine bone slices for 0.5-1 h. After removing nonadherent cells by vigorous washing, osteoclasts attached to the bone slices were treated with antisense and sense oligonucleotides for 2 days.…”
Section: Methodsmentioning
confidence: 99%
“…A Pit Assay-Bone resorption was determined by a pit assay as described (12). Osteoclasts were isolated from the bone marrow of 4 -6-day-old neonatal mice and placed on bovine bone slices for 0.5-1 h. After removing nonadherent cells by vigorous washing, osteoclasts attached to the bone slices were treated with antisense and sense oligonucleotides for 2 days.…”
Section: Methodsmentioning
confidence: 99%
“…However, its effects on osteoclast formation are controversial. IFN-γ also enhances osteoclast generation in cultures of peripheral blood from osteopetrotic patients, in part by normalizing superoxide production (57) and has been shown to be efficacious in the treatment of osteoporosis in humans (58). A recent study analyzed the in vivo effects of IFN-γ in 3 mouse models of bone loss, including ovariectomy, LPS injection, and inflammation induced by silencing TGF-β signaling in T cells.…”
Section: Ranklmentioning
confidence: 99%
“…In contrast, Gao et al (12) recently found that IFN-␥ indirectly stimulates osteoclast formation and bone loss after ovariectomy via antigen-driven T cell activation, resulting in the production of osteoclast-activating factors. Interestingly, IFN-␥ has been used to treat infantile osteopetrosis in which patients suffered from high bone mass secondary to osteoclast dysfunction or osteoblast hyperactivity, but the mechanism of action may be through modulation of the host immune system rather than direct effects on bone cells (13)(14)(15). However, the role of IFN-␥ in the treatment of osteolytic bone metastases has not been elucidated.…”
Section: Ifn-␥mentioning
confidence: 99%